Factors Affecting Customer Loyalty at Bakso Anna Viral Bengkulu - Salsabila, Aldy Andhika; Irwanto , Tito; Zoniarti , Zoniarti (Universitas Dehasen Bengkulu, 2025)
The importance of customer loyalty in the culinary business, especially in the face of fierce competition. Issues at Bakso Anna Viral Bengkulu include perceived value, product quality, price, and customer satisfaction, which affect loyalty. The research questions and objectives are aimed at testing the influence of these variables. This study is limited to quantitative methods using a survey approach (questionnaire) and purposive sampling techniques. The sample consists of 100 respondents who have purchased Bakso Anna Viral at least three times. The instruments were tested for validity and reliability using SPSS. Data analysis was conducted using multiple linear regression, T-test (partial), F-test (simultaneous), and the coefficient of determination R². The results of the multiple linear regression show the equation: Y = 1.883 + 0.210 X1 + 0.257 X2 + 0.227 X3 + 0.206 X4, indicating a positive regression direction, meaning that the variables of perceived value (X1), product (X2), price (X3), and customer satisfaction (X4) have a positive influence on customer loyalty to Anna Viral Bengkulu meatballs. The coefficient of determination (R-squared) value from SPSS 25.00 is 0.924. This means that perceived value, product, price, and customer satisfaction influence customer loyalty by 92.4%, while the remaining 7.6% is influenced by other factors. The results of the t-test at a significance level of 0.05 indicate that, individually, X1, X2, X3, and X4 have a significant influence on customer loyalty toward Anna Viral Bengkulu meatballs, with values of X1 = 0.004, X2 = 0.005, X3 = 0.014, and X4 = 0.018